KULA KIBI SEBAGAI BENTUK TRADISI LISAN MASYARAKAT DESA TENDA KECAMATAN WOLOJITA KABUPATEN ENDE - Dominika Dhapa; Maria Polencys Pere Ri’a (Universitas Islam Negeri Mataram, 2021)
This study aims to describe and analyze the form and meaning oftraditional speech in ritual kula kibi Village TendaKecamatan Wolojita Ende.Penelitian using a qualitative approach.Data collected using key informants.Data collected through interviews and field observations.Presentation ofresults after data analyzed then the data presented using words or sentences.The result of research about the form of Tuturan adat kula kibi is (1)phonologidari form of speech of traditional ceremony kula kibi communityof Tenda Village Wolojita District Ende. (2) the morphological form of thetraditional ceremony kula kibi speech of the community of Tenda Village,Wolojita Sub-district, Ende Regency. (3) the syntactic form of the traditionalceremony kula kibi speech of the village of Tenda District Wolojita EndeDistrict. The meanings of the customs of the kula kibi are (1) Believing inthe supreme being (Ia). (2) Believe in the ancestors ‘Embu Mamo’. (3) Believein customs. (4) the meaning of togetherness (5) the meaning of hope forsuccess.